Neuroproteção do cassis (Ribes nigrum L.) e de sua associação com o Donepezil em modelo de amnésia induzida por escopolamina - Costa, Pauline da (2019)
Memory deficits that occur with the process of aging could also be associated with the pathophysiology of neurodegenerative diseases, such as Alzheimer’s disease (AD). AD is characterized by the progressive deterioration of memory and other cognitive functions, which could present multiple factors, such as the impairment of cholinergic neurotransmission and the excess of reactive species in the central nervous system. Besides, it has been proposed the involvement of the purinergic system in several pathological processes as neurodegeneration. Cholinesterase inhibitor drugs, such as Donepezil (DNPZ), are used in the treatment of AD symptoms; however, they could present adverse effects. Blackcurrant (Ribes nigrum L.) is a fruit with a high content of bioactive compounds mainly anthocyanins such as cyanidin and delphinidin, with antioxidant, anti-inflammatory and neuroprotective properties. The objective of this study was to evaluate the neuroprotective effects of Blackcurrant and of its association with DNPZ on the cognitive impairment, cholinergic and purinergic signaling, as well as to analyze the anti-inflammatory and antioxidant responses in an amnesia model induced by the chronic administration of scopolamine in mice. Male adult Swiss mice previously received Blackcurrant (50 or 100 mg/kg) or saline (10 mL/kg), orally, once a day for 7 days. Posteriorly, in addition to Blackcurrant, DNPZ (5 mg/kg; orally) and Scopolamine (SCO; 1 mg/kg, i.p.) were administered once a day for a further 21 days. SCO was administered thirty minutes after Blackcurrant and DNPZ to induce amnesia model, due to its antagonist effect on acetylcholine muscarinic receptors. This model was validated by behavior tests: Y-maze, open field, object recognition, Morris water maze and inhibitory avoidance. The experimental protocol had a total duration of 28 days. Results of behavioral tests showed that the treatment with Blackcurrant and/or prevented learning and memory deficits induced by SCO. This model caused damages to the cholinergic system, increasing the activity of acetylcholinesterase (AChE) and butyrylcholinesterase enzymes, besides reducing the expression of choline acetyltransferase in the hippocampus, and increasing AChE expression and density in the cerebral cortex and hippocampus of mice. However, the treatment with Blackcurrant and/or DNPZ prevented these deleterious effects to cholinergic enzymes. Additionally, the treatment with Blackcurrant and/or DNPZ prevented the decrease in the NTPDase activity (ATP and ADP) and the increase in the activity of adenosine deaminase in synaptosomes of cerebral cortex, as well as decreasing the density of P2X7 and A2A receptors in the cerebral cortex of mice with cognitive damages induced by SCO. The treatment with Blackcurrant and/or DNPZ also avoided the pro-inflammatory responses induced by SCO, reducing the expression of the inflammatory markers such as Nod-like receptor protein 3 (NLRP3) inflammasome and interleukin-1β in the cerebral cortex. Furthermore, Blackcurrant and/or DNPZ promoted antioxidant effects, inhibiting SCO effects on the glutathione system and decreasing oxidative stress parameters in the cerebral cortex and/or hippocampus. The results of this study were similar to the found with treatment with the standard drug DNPZ. Based on the results, it is suggested that Blackcurrant and/or DNPZ exerted anti-amnesic effects by the modulation of cholinergic and purinergic system, preventing the pro-inflammatory responses and oxidative stress. Therefore, Blackcurrant could be considered as promising therapeutic agent in the prevention of memory deficits.